2019
DOI: 10.2147/hp.s217569
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hypoxia Suppresses High Fat Diet-Induced Steatosis And Development Of Hepatic Adenomas</p>

Abstract: PurposeNonalcoholic fatty liver disease (NAFLD) is considered the most common form of silent liver disease in the United States and obesity is associated with increased risk of NAFLD. Obstructive sleep apnea (OSA) which is common in obese individuals is associated with a greater incidence of NAFLD, which in turn, increases the risk for hepatocellular carcinoma (HCC). It is unclear how obesity, OSA and NAFLD interrelate nor how they collectively contribute to an increased risk for developing HCC.Patients and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These 19 DEGs enriched to metabolism are primarily involved in insulin sensitivity, lipid accumulation, glycogen storage, and energy expenditure. Previous studies reported that the down-regulation of ALOX15 in alcohol-induced mice liver damage [ 18 ], CA9 in BALB/c mice [ 19 ], TH in nonalcoholic fatty liver disease (NAFLD) [ 20 ], HKDC1 [ 21 ], and the up-regulation of UGDH [ 22 ] can significantly relieve oxidative stress, lipid accumulation, and liver damage. Knockdown of NDUFA4L2 suppressed ROS accumulation and apoptosis in hepatocellular carcinoma (HCC) cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These 19 DEGs enriched to metabolism are primarily involved in insulin sensitivity, lipid accumulation, glycogen storage, and energy expenditure. Previous studies reported that the down-regulation of ALOX15 in alcohol-induced mice liver damage [ 18 ], CA9 in BALB/c mice [ 19 ], TH in nonalcoholic fatty liver disease (NAFLD) [ 20 ], HKDC1 [ 21 ], and the up-regulation of UGDH [ 22 ] can significantly relieve oxidative stress, lipid accumulation, and liver damage. Knockdown of NDUFA4L2 suppressed ROS accumulation and apoptosis in hepatocellular carcinoma (HCC) cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Such perspective calls for a more in-depth understanding of the molecular and cellular mechanisms that underpin the relationship between OSA and cancer biology before embarking on a large and expensive cohort. 11,12 While limitations of space and competence in the area of cancer biology prevent us from delving deeper, it would suffice to say that the work by Marshall et al has spurred intense investigation into this important area.…”
mentioning
confidence: 99%